Coping with COVID-19 in an international border region: health and economy - Reinaldo Antonio Silva-Sobrinho; Adriana Zilly; Rosane Meire Munhak da Silva; Marcos Augusto Moraes Arcoverde; Enrique Jorge Deschutter; Pedro Fredemir Palha; Angela Sobral Bernardi (Universidade de São Paulo, 2021)
Objective: to analyze how the social isolation measures and closed borders affected the health and economy in an international border region. Method: descriptive cross-sectional study conducted in the western region of Paraná, Brazil, using an electronic form created using Google® forms. A sample of 2,510 people was addressed. Descriptive analysis and the Chi-square test were performed, with a level of significance established at 5%. This public opinion survey, addressing unidentified participants, is in accordance with Resolutions 466/2012 and 510/2016. Results: the participants were 41.5 years old on average, most were women and worked in the education sector; 41.9% reported that the closing of borders/commercial businesses negatively influenced income; 17.7% reported the possibility of losing their jobs; 89.0% consider that a larger number of people would be sick if the borders/commercial had not been closed; 63.7% believe the health services are not prepared to deal with the pandemic; 74.9% realize that the Brazilian Unified Health System may not have sufficient service capacity; 63.4% reported anxiety; and 75.6% of commercial workers will experience changes in their income level. Conclusion: the closing of international borders and commercial businesses was related to a perception of physical and mental changes, job loss, and decreased income.